Biosystem with 16 highly selective optical channels for biological fluids analysis in the visible spectrum - Minas, Graça (2003)
This paper reports a biosystem (biological system) for analyzing biochemical substances in biological fluids. Rather than one channel, it comprises 16 highly selective optical channels that enable the measurement of the concentration of 16 different biochemical substances. An array of 16 optical filters with high reflectivity and low absorption loss has been designed using dielectric films. Each filter is sensitive in a single wavelength with a FWHM (Full Width Half Maximum) < 5 nm and peak intensity > 52%. A commercially available band pass optical filter with a band pass wavelength in 450 600 nm is used to enable the use of a white light source for biosystem illumination. Preliminary tests with a single channel are successfully demonstrated.